Preparación de complejos de coordinación a partir de productos naturales - Nava Andrade, Karina (Universidad Michoacana de San Nicolás de Hidalgo, 2016)
In the present work the reactivity of natural terpenes isoabienol (1), beyerenoic acid (2) and kaurenoic acid (3) toward ZnCl2 and IrCl3 is described. In the study of the terpenes 1-3 with ZnCl2, the diamagnetic complexes [ZnCl2(isoabienol)2] (4), [Zn4O(beyerenate)6] (6) and [Zn4O(kaurenate)6] (8) were obtained. The 1H NMR spectrum of 4 suggested the coordination of 1 toward Zn(II) through the hydroxyl group and the double bond C-13/C-16. The carboxylates 5 y 7, generated in situ, allowed the formation of the clusters 6 and 8, respectively; their structural characterization was confirmed by single-crystal X-ray diffraction analysis. Interaction of the terpenes 1-3 with IrCl3 gave rise to catalysis products, which were identified by its NMR data. The ciclization of isoabienol (1) catalyzed by iridium generated the 13-epi-manoyl oxide (9) and manoyl oxide (10). In the reaction of the terpenes 2 and 3 with IrCl3, the beyeranoic acid (11), 16?-kauranoic acid (12) and 16?-kauranoic acid (13) were obtained; which revealed a possible methodology for the olefins hydrogenation catalyzed by iridium in conditions of green chemistry. In the transterification catalytic assays, the compounds [Zn4O(beyerenato)6] (6) and [Zn4O(kaurenato)6] (8) showed high catalytic activity in the transterification of glycerin tricaprylate with methanol; due to this, they are promising catalysts in the biodiesel production starting from vegetable oils.

El presente trabajo describe la reactividad de los diterpenos naturales isoabienol (1), ácido beyerenoico (2) y ácido kaurenoico (3) frente a la sales de ZnCl2 y IrCl3. En el estudio de los terpenos 1-3 con ZnCl2, se obtuvieron los complejos diamagnéticos [ZnCl2(isoabienol)2] (4), [Zn4O(beyerenato)6] (6) y [Zn4O(kaurenato)6] (8). El espectro de RMN 1H de 4 sugirió la coordinación de 1 al Zn(II) a través del grupo hidroxilo y el doble enlace C-13/C-16. Los carboxilatos 5 y 7, generados in situ, propiciaron la formación de los complejo 6 y 8, respectivamente; su caracterización estructural se confirmó por difracción de rayos X de monocristal. La interacción de los diterpenos 1-3 con el IrCl3 dio lugar a productos de catálisis, los cuales fueron identificados por RMN de 1H y de 13C. La ciclización del isoabienol (1) catalizada por iridio generó los compuestos óxido de 13-epi-manoilo (9) y óxido de manoilo (10). En la reacción de los terpenos 2 y 3 con IrCl3 se obtuvieron los ácidos beyeranoico (11), 16α-kauranoico (12) y 16β-kauranoico (13), que revelaron una posible metodología para la hidrogenación de olefinas catalizada por iridio bajo condiciones de química verde. En los ensayos catalíticos, los complejos [Zn4O(beyerenato)6] (6) y [Zn4O(kaurenato)6] (8) exhibieron actividad catalítica alta en la reacción de transesterificación de tricaprilato de glicerina con metanol; por tanto, son catalizadores prometedores en la producción de biodiesel a partir de aceites vegetales.
Instituto de Investigaciones Químico Biológicas. Maestría en Ciencias Químicas
Keywords: info:eu-repo/classification/cti/2; IIQB-R-M-2016-0476; Diterpenos; Cúmulo; Zinc; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/2329